Judaísmo (im)possível? Ressignificação das práticas judaicas sob a ótica feminina na primeira visitação do Santo Ofício a Pernambuco colonial (1593- 1595) - Diniz, Bruna Sousa (2021)
This dissertation studies the redefinition of Jewish practices according to the role of New Christian women living in the capital of Pernambuco during the 16th century. With the banning of the free Hebrew creed in Portuguese domains, the conversion of followers of that religion into New Christians and, later, with the establishment of the Inquisition in Portugal, many saw in the Brazilian lands a possibility of distancing themselves from the action of the Holy Office and reach better favorable and social conditions. In Pernambuco's space, the attitudes considered Judaizing would be revived by an expressive index of neoconversations. Women's action in the maintenance of these rites was once linked to the functions assigned to the Jews: the education of children and the preservation of Judaism in the home environment. In this sense, they were great propagators of the customs and ceremonies of the forbidden faith, considering that, having prevented Judaism in the open, the domestic environment was dimensioned as a stronghold to provide opportunities for the conservation of knowledge that referred to that religion. However, as Hebrew practices remembered on colonial soil they did not take on a single expression. There are several ways to Judaize, from a conscious return to ancestral faith, to passing on customs automatically. From this perspective, we analyze the intimate universe of three New Christian families, the Dias Fernandes, the Álvares Soeiro and the Fernandes do Casal, whose matriarchs transmitted to their female offspring, each with its particularities, teachings considered heretical. The validation of the homemade cases was possible based on the testimonies addressed to the visitor's table and documented by the inquisitorial retinues, during the first visitation of the Holy Office to parts of Brazil. The results obtained from a survey enabled the construction of a learning object for students in primary education.